Iconicity as Multimodal, Polysemiotic, and Plurifunctional - Hodge, Gabrielle; Ferrara, Lindsay (Frontiers in Psychology, 2022)
Investigations of iconicity in language, whereby interactants coordinate meaningful bodily actions to create resemblances, are prevalent across the human communication sciences. However, when it comes to analysing and comparing iconicity across different interactions (e.g., deaf, deafblind, hearing) and modes of communication (e.g., manual signs, speech, writing), it is not always clear we are looking at the same thing. For example, tokens of spoken ideophones and manual depicting actions may both be analysed as iconic forms (see e.g., Schembri, et al., 2005; Dingemanse, 2013). Yet spoken ideophones may signal depictive and descriptive qualities via speech, while manual actions may signal depictive, descriptive and indexical qualities via the shape, movement and placement of the hands in space. Furthermore, each may co-occur with other semiotics articulated with the face, hands and body within composite utterances (Enfield, 2009). The paradigm of iconicity as a single property is too broad and coarse for comparative semiotics, as important details necessary for understanding the range of human communicative potentialities may be masked. Here we draw on semiotic approaches to language and communication, including Clark’s (1996) model of language as signalled via describing, indicating and/or depicting and Silverstein’s (1976) notion of non-referential indexicality, to illustrate the multidimensionality of iconicity in co-present interactions. This builds on our earlier proposal for analysing how different methods of semiotic signalling are combined in multimodal language use (Ferrara & Hodge, 2018). We discuss some implications for the language and communication sciences and explain how this approach may inform a theory of biosemiotics.